Antitumour activity of somatostatin analogues in sporadic, progressive, metastatic pulmonary carcinoids. (April 2017) - Sullivan, Ivana; Le Teuff, Gwénaël; Guigay, Joël; Caramella, Caroline; Berdelou, Amandine; Leboulleux, Sophie; Déandréis, Désirée; Hadoux, Julien; Ducreux, Michel; Duvillard, Pierre; Adam, Julien; Scoazec, Jean-Yves; et al.
Abstract: Purpose: Antiproliferative activity of somatostatin analogues (SSAs) has been demonstrated in digestive neuroendocrine tumours but few data have been published on pulmonary carcinoids (PC). The aim of this retrospective study was to report the antitumour activity of SSAs in patients with progressive, metastatic PC. Methods: Patients with PC and treated with SSA monotherapy were reviewed. Disease was classified according to the tumour slope prior to SSA initiation as rapidly progressive (at least 20% increase in the sum of the longest diameter of target lesions or the appearance of one or more new lesions within 6 months) or slowly progressive (if progression occurred over 6 months). Survival outcomes were progression-free survival (PFS) and overall survival (OS). We additionally examined the overall response rate and safety. Prognostic factors associated with PFS and OS were sought. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using the Cox model. Results: Among 67 patients reviewed, 61 were included in the study. Forty-one (67%) of them exhibited slowly progressive disease prior to SSAs, 41 (67%) had atypical carcinoids and 29 (48%) had functioning tumours. Forty-six (76%) patients had received SSAs as first-line therapy. The best overall response was stable disease in 47 (77%) patients. The median duration of SSAs was 13.7 months. With a median follow-up of 5.8 years, median PFS and OS were 17.4 (95% CI: 8.7–26.0) and 58.4 (95% CI: 44.2–102.7) months, respectively. Functioning tumours and slowly progressive disease were significantly associated with longer PFS: HR = 0.48 ([95% CI: 0.24–0.95], p  = 0.03) and HR = 7.43 ([95% CI: 3.02–18.25], p  < 0.0001), respectively. Only functioning tumours remained significantly associated with OS: HR = 0.33 ([95% CI: 0.14–0.79], p  = 0.01). Treatment had been discontinued in two patients due to side-effects. Conclusions: Median PFS observed in our study is encouraging for PC patients. Patients with functioning tumours and slowly progressive disease treated with SSAs have better prognosis. Highlights: SSAs yielded a clinically meaningful overall progression-free survival in progressive, metastatic pulmonary carcinoids. The results are encouraging, particularly in patients with functioning tumours and slowly progressive disease prior to SSAs. Our results reproduce the antiproliferative benefit observed with SSAs in digestive neuroendocrine tumours.